SYSTEMATIC LITERATURE REVIEW : LANDASAN FILOSOFIS PENDIDIKAN DAN IMPLEMENTASI KURIKULUM MERDEKA DALAM MEWUJUDKAN SDM UNGGUL DI ERA SOCIETY 5.0. - Zalma Niendya Pangestika; Maulidina, Rista; Nur Khayati, Afif; Oktarina, Nina; Widodo, Joko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The independent curriculum is the main problem of educational units which originates from the philosophy of education in responding to developments over time. This research aims to review the literature on the philosophical foundations of education that support the implementation of independent campuses to create superior human resources 5.0. In the midst of globalization and industrial revolution 4.0, education must adapt to the demands of relevant skills and competencies. The method used is Systematic Literature Review from journal sources 2018-2023 with help of the application publish or perish, then identify the appropriateness test data obtained from 15 journals that match literature objectives. This research explores philosophies such as constructivism, pragmatism, and humanism that emphasize active and collaborative learning. Independent campus research results open opportunities for developing interpersonal skills in human resources. The research conclusion explains the importance of education based on a strong and innovative philosophy that will increase the competitiveness of the quality of Indonesian human resources at the global level. It is hoped that these findings can serve as a guide for developing education policies that are more responsive to the needs of society and industry, and support the achievement of the vision of superior human resources 5.0.